Building a Culture of Innovation in Higher Education: The Role of Organizational Innovativeness Climate, Motivation to Learn, and Knowledge sharing in Pushing Innovative Work Behaviour - Wati, Linda; Dharma, Surya; Jadmiko, Purbo; Windi, Afifah (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
Innovative work behaviour in higher education is an important aspect that requires attention. The study of innovative work behaviour in higher education is very important to foster a culture of creativity and progress. This research aims to identify lecturers who have innovative behaviour and provide rewards or support for their development. This can encourage professional growth and increase the competence of lecturers, thereby creating superior human resources in the field of higher education. The Sample in this research were lecturers who worked at private universities in the LLDIKTI X Region. Sample selection used probability sampling techniques with random sampling. Research hypothesis testing was carried out using the Multiple Linear Regression Analysis model. Multiple Linear Regression Analysis is used to measure the influence between variables of organizational Innovativeness Climate, Motivation to Learn, and Knowledge Sharing towards Innovative Work Behaviour. The results of this research organizational Innovativeness Climate, Knowledge Sharing, and Motive to Learn significantly influence Innovative Work Behavior. The test results show that the three independent variables have a positive and significant influence on the level of innovative behaviour of lecturers in the workplace.